Islamic Character Education Model Based on Rumah Qur'an for Early Childhood - Muhammad Asmariadi Arsyad; Katni Katni; Sigit Dwi Laksana (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
Islamic character education in early childhood plays a crucial role in shaping children's moral, spiritual, and social development. Amid the challenges of globalization and rapid technological advancement that may negatively influence children's behavior, an educational model that integrates Islamic values into daily life is increasingly needed. This study aims to analyze the Islamic character education model implemented in Rumah Qur'an institutions for early childhood learners, identify the character values developed through educational activities, and examine the supporting and inhibiting factors affecting its implementation. This study employed a qualitative approach using a library research design. Data were collected from scholarly journals, academic books, and other relevant publications related to Islamic character education, early childhood education, and Rumah Qur'an institutions published between 2018 and 2026. Data were analyzed using content analysis techniques through data reduction, data display, and conclusion drawing. The findings indicate that Islamic character education in Rumah Qur'an is implemented through role modeling (uswah hasanah), habituation, Qur'anic value-based learning, and collaboration between educators and parents. The character values developed include religiosity, discipline, honesty, responsibility, politeness, and social care. A supportive religious environment and active parental involvement were identified as major supporting factors, while uncontrolled digital media exposure, limited family support, and differences in children's characteristics emerged as significant challenges